2018
DOI: 10.5007/2175-7941.2018v35n2p532
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de gráficos da cinemática através do jogo batalha naval e de atividades robóticas

Abstract: A experiência didática descrita e analisada neste artigo foi desenvolvida em uma escola estadual do município de Candiota, RS, no formato de dois módulos didáticos, contendo atividades para a introdução ao ensino do plano cartesiano e de gráficos de Cinemática. No primeiro módulo, enfatizou-se o estudo de coordenadas cartesianas, utilizando o jogo batalha naval e a construção de um plano cartesiano no pátio da escola. No segundo módulo, abordou-se a elaboração e a interpretação de gráficos em Cinemática, com ê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(3 reference statements)
0
1
0
Order By: Relevance
“…The t test indicated the existence of a statistical difference between the scores (t test 4.259 for df = 15 and p = 0.001) which, according to the authors, indicates that the sequence contributed to an improvement in learning. Dworakowski et al (2018) reported the results of a didactic sequence, applied to a class of 39 students (with ages between 14 years and 16 years old) in the form of two modules. The first had an emphasis on the study of Cartesian coordinates through a game of naval battle held in the schoolyard.…”
Section: Educational Robotics To Teach Graphics In Kinematicsmentioning
confidence: 99%
“…The t test indicated the existence of a statistical difference between the scores (t test 4.259 for df = 15 and p = 0.001) which, according to the authors, indicates that the sequence contributed to an improvement in learning. Dworakowski et al (2018) reported the results of a didactic sequence, applied to a class of 39 students (with ages between 14 years and 16 years old) in the form of two modules. The first had an emphasis on the study of Cartesian coordinates through a game of naval battle held in the schoolyard.…”
Section: Educational Robotics To Teach Graphics In Kinematicsmentioning
confidence: 99%